2018
DOI: 10.1007/s12223-018-0585-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent perspectives on the molecular basis of biofilm formation by Pseudomonas aeruginosa and approaches for treatment and biofilm dispersal

Abstract: Pseudomonas aeruginosa, a Gram-negative, rod-shaped bacterium causes widespread diseases in humans. This bacterium is frequently related to nosocomial infections such as pneumonia, urinary tract infections (UTIs) and bacteriaemia especially in immunocompromised patients. The current review focuses on the recent perspectives on biofilms formation by these bacteria. Biofilms are communities of microorganisms in which cells stick to each other and often adhere to a surface. These adherent cells are usually embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 163 publications
2
98
0
7
Order By: Relevance
“…In agreement with this, we found that out of the seven strains which were multi-drug resistant, five were exoU positive. Moreover, these MDR isolates formed moderate to strong biofilms which is consistent with association of biofilm formation with antibiotic resistance reported previously [19]. Swarming has also been associated with increased antibiotic resistance [12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with this, we found that out of the seven strains which were multi-drug resistant, five were exoU positive. Moreover, these MDR isolates formed moderate to strong biofilms which is consistent with association of biofilm formation with antibiotic resistance reported previously [19]. Swarming has also been associated with increased antibiotic resistance [12].…”
Section: Discussionsupporting
confidence: 89%
“…Pseudomonas spp. are also known to form biofilms that prevent the penetration of antibiotics contributing to its virulence and are notoriously difficult to eradicate [19]. LadS, a calcium-responsive kinase is required for biofilm formation and is responsible for the swirtch in acute-chronic Pseudomonas infection [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…; Skariyachan et al . ). Thus, a biofilm provides P. aeruginosa a protective mode of growth, where individual bacteria can reproduce while circumventing external stresses.…”
Section: Introductionmentioning
confidence: 97%
“…Bacteria in a biofilm display many different features from their planktonic counterparts. These structured and aggregated bacterial communities are known to be notorious for their resistance to a variety of antibiotics and the action of host defences (Singh et al 2017;Skariyachan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These GGDEF or EAL domains, in tandem with other signaling domains and located in the cytoplasm or cytomembranes, precisely regulate local intracellular c-di-GMP concentrations by responding to diverse upstream activating signals. C-di-GMP regulates a variety of physiological processes, including cell-cell interactions (Matsuyama et al, 2016; Lin C. S. et al, 2017), biofilm formation and dispersal (Ha and O'Toole, 2015; Skariyachan et al, 2018), cell motility (Orr and Lee, 2016), and the responses to a variety of external stimulation, such as oxygen (Burns et al, 2016), nitric oxide (Rinaldo et al, 2018), and light (Blain-Hartung et al, 2017). The c-di-GMP signaling pathway is present in many Gram-negative bacteria but is less reported in Gram-positive bacteria (Purcell and Tamayo, 2016).…”
Section: Introductionmentioning
confidence: 99%